Stability, survival, and patient satisfaction with CAD/CAM versus conventional multistranded fixed retainers in orthodontic patients: a 6-month follow-up of a two-centre randomized controlled clinical trial. (14th August 2022) - Gera, Arwa; Pullisaar, Helen; Cattaneo, Paolo M; Gera, Shadi; Vandevska-Radunovic, Vaska; Cornelis, Marie A
Summary: Objectives: The primary aim of this two-arm parallel two-centre randomized controlled trial was to compare computer-aided design and computer-aided manufacturing (CAD/CAM) versus conventional multistranded fixed retainers (FRs) in terms of stability over 6 months. Secondary outcomes were failure rates and patient satisfaction. Methods: Patients were randomized to CAD/CAM or conventional FRs in both arches, in 1:1 ratio and blocks of four. Allocation concealment was secured by using sequentially numbered envelopes. Patients were blinded. Retainers were bonded at the end of orthodontic treatment (T0), and patients were recalled after 1 (T1), 3 (T3), and 6 (T6) months. First-time retainer failures were recorded and digital impressions were taken. Arch widths and lengths, as well as Little's Irregularity Index (LII), were measured. Additionally, patients answered satisfaction questionnaires. Linear mixed models were applied for measurements and patient satisfaction. Survival analyses were estimated with Kaplan-Meier curves, along with Cox-regression modelling. Results: One hundred and eighty-one patients were randomized (98 in Centre 1, and 83 in Centre 2): Ninety in the CAD/CAM group and 91 in the conventional group. Three subjects dropped out at baseline, as they did not attend any of the follow-up appointments.168 patients attended the T6 visit. There were no significant differences in arch dimensions between T0 and T6, whilst the LII was different only in the CAD/CAM group (mean difference: 0.2 mm; 95% confidence interval: 0.1 to 0.4; P < 0.001). Within 6 months, 39 upper retainers (19 out of 88 CAD/CAM and 20 out of 90 conventional retainers) and 52 lower retainers failed (26 out of 88 CAD/CAM and 26 out of 90 conventional retainers), with no significant difference between the survival of both types of retainers (hazard ratios conventional to CAD/CAM: upper arch: 0.99 [ P =0.99], lower arch: 0.93 [ P = 0.80]). There were no significant changes in patient satisfaction between the groups. No harms were observed. Conclusions: There were no clinically significant differences in LII, arch widths and lengths between CAD/CAM and conventional retainers after 6 months. There was no difference in failures and in patient satisfaction between both types of FRs. Registration: ClinicalTrials.gov NCT04389879.